S(e_n) = (-1)^n h_n, and a mistake in lecture

1. In class I explained that S(e_{\lambda}) = (-1)^n h_{\lambda} for any partition \lambda of n, and that this follows from the equation

\sum_{k=0}^n (-1)^k h_k e_{n-k} = 0

for n \geq 1. Can someone provide a proof of this?

(Hint: there are elegant formulas for the generating functions \sum_n e_nt^n and \sum_n h_nt^n.)

2. I made a mistake in defining the inner product on Sym. I meant to decree that m_{\lambda} and h_{\lambda} are dual bases. (I wrote e instead of m). So we have:

\langle m_{\lambda}, h_{\mu} \rangle = 1 if \lambda = \mu, and \langle m_{\lambda}, h_{\mu} \rangle = 0 if \lambda \neq \mu.


One comment

  1. Pingback: Two important comments on the scalar product « hopf algebras and combinatorics

Leave a Reply

Fill in your details below or click an icon to log in:

WordPress.com Logo

You are commenting using your WordPress.com account. Log Out /  Change )

Google+ photo

You are commenting using your Google+ account. Log Out /  Change )

Twitter picture

You are commenting using your Twitter account. Log Out /  Change )

Facebook photo

You are commenting using your Facebook account. Log Out /  Change )


Connecting to %s

%d bloggers like this: